Sexual dimorphism applying the mandibular canine index in a Brazilian sample: a pilot study - Luciana Vigorito Magalhães; Bruna Saud Borges; Paulo Henrique Viana Pinto; Caroline Paula Alves; Ricardo Henrique Alves da Silva (Universidade Estadual de Maringá, 2021)
The aim of this study was to apply the morphometric quantification of the canine index for sexual dimorphism in a Brazilian sample. The sample consisted of 90 participants (45 males and 45 females) aged between 18 and 35 years. With the aid of a digital caliper, the intraoral mesio-distal measurement of the permanent mandibular right canine (MD43) and the intercanine distance (IC) were taken by three examiners. The measurements were used in a formula established by Rao, Rao, Pai e Kotian (1989) to estimate sex based on morphometric features of the human canines. The applicability of this approach for sexual dimorphism was assessed based on the inherent mandibular canine index (MCI) calculated by the formula. The MCI was higher in males than females. The mean general accuracy rate of the MCI for sexual dimorphism in the total sample was 52.22%. In males, the MCI was able to properly distinguish sex in 82.22% of the sample, while in females the accuracy decreased to 22.22%.  These outcomes raise the attention for the careful use of the MCI in practice - especially in the field of Forensic Anthropology. In particular, the accuracy of the method was close to random in a sample that contained both sexes. Thus, MCI should not be used as the only tool for sexual dimorphism.